Groundwater Resilience Study for Sustainable Tourism Development Through Electrical Sounding Method in Mansinam Island, Manokwari Regency, West Papua, Indonesia - Aziz, Faishal; Nugraha, Bayu; M I, Teuku Yan Waliana; Restu, Abigail; Barkah, Mochamad Nursiyam; Hadian, Mohamad Sapari Dwi (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
The sustainable exploitation of groundwater must be understood based on an understanding of geology and hydrogeological conditions. Water availability on small islands has limited reserves and is vulnerable to contamination. In addition, groundwater resources are vulnerable to decreasing groundwater levels in high abstraction without good management practices. Mansinam Island is one of the islands administratively located in Doreri Bay – Manokwari Regency for sustainable tourism development, which has an area of 410.97 Ha. The purpose of this research is to determine the condition and potential of groundwater in the Mansinam Island area. The geoelectric method is a technique that is widely used to characterize groundwater resources, which aims to identify the physical parameters of the subsoil and acquire information about its natural properties. The resistivity values obtained from the field measurement are thus interpreted and determined to be further correlated with geological characteristics as well as aquifer characteristics. On 11 geoelectric paths, good results are presented with a measurement depth of 20 – 23m. The northern area of the measurement on Mansinam Island has a resistivity value of 58.6 - 100Ωm for an aquifer layer containing groundwater potential with a groundwater level (MAT) of 12-20m and aquifer thickness of 3-8m. Meanwhile, the southern area of the geoelectric measurement has a resistivity value of 25.5-100Ωm for an aquifer layer containing groundwater potential, with a groundwater level of 6-12m and aquifer thickness of 8-16m. The southern segment of Mansinam Island has better potential for groundwater, with a relatively shallower depth and thicker aquifer than the northern segment.